A simple vapor‐diffusion method enables protein crystallization inside the HARE serial crystallography chip. Issue 6 (24th May 2021) - Norton-Baker, Brenna; Mehrabi, Pedram; Boger, Juliane; Schönherr, Robert; von Stetten, David; Schikora, Hendrik; Kwok, Ashley O.; Martin, Rachel W.; Miller, R. J. Dwayne; Redecke, Lars; Schulz, Eike C.
Abstract : The in‐chip crystallization and structure determination of four different soluble proteins and an intracellular protein using serial synchrotron crystallography is reported. Abstract : Fixed‐target serial crystallography has become an important method for the study of protein structure and dynamics at synchrotrons and X‐ray free‐electron lasers. However, sample homogeneity, consumption and the physical stress on samples remain major challenges for these high‐throughput experiments, which depend on high‐quality protein microcrystals. The batch crystallization procedures that are typically applied require time‐ and sample‐intensive screening and optimization. Here, a simple protein crystallization method inside the features of the HARE serial crystallography chips is reported that circumvents batch crystallization and allows the direct transfer of canonical vapor‐diffusion conditions to in‐chip crystallization. Based on conventional hanging‐drop vapor‐diffusion experiments, the crystallization solution is distributed into the wells of the HARE chip and equilibrated against a reservoir with mother liquor. Using this simple method, high‐quality microcrystals were generated with sufficient density for the structure determination of four different proteins. A new protein variant was crystallized using the protein concentrations encountered during canonical crystallization experiments, enabling structure determination from ∼55 µg of protein. Additionally, structure determination from intracellular crystals grown in insect cells cultured directly in the features of the HARE chips is demonstrated. In cellulo crystallization represents a comparatively unexplored space in crystallization, especially for proteins that are resistant to crystallization using conventional techniques, and eliminates any need for laborious protein purification. This in‐chip technique avoids harvesting the sensitive crystals or any further physical handling of the crystal‐containing cells. These proof‐of‐principle experiments indicate the potential of this method to become a simple alternative to batch crystallization approaches and also as a convenient extension to canonical crystallization screens.